No boys allowed - Levinson, Marilyn (Mahwah, N.J. : Bridgewater Press, 2005)
When her father leaves the family to marry a younger woman, eleven-year-old Cassie Landauer feels she can't trust any male, including her best friend, until her great-uncle helps her put the changes in her life in perspective.
G5
Keywords: Divorce -- Fiction; Family life -- Fiction; Interpersonal relations -- Fiction; Great-uncles -- Fiction